TYPE 1 DIABETES - A CASE STUDY - JUDY HANDLY (International Journal of Pharma and Bio Sciences, 2016)
Diabetes mellitus is a heterogeneous group of diseases characterized by high blood glucose levels due to defects in insulin secretion, insulin action, or both. Our bodies need fuel for proper function. Glucose is the fuel that our cells use to produce energy. In order to process the sugar we eat in various foods, our bodies produce insulin. Insulin is a hormone made by beta cells, clusters of cells in the pancreas1 . In type 1 diabetes, the beta cells in the pancreas are unable to make insulin because of autoimmune disease. This means that the body’s immune system makes autoantibodies that attack and destroy the pancreatic beta cells. Type 2 diabetes is the result of the body’s inability to properly use the insulin made by the pancreas and almost always occurs in adults and children who are overweight. Because type 1 diabetes usually starts in childhood, it is sometimes called juvenile diabetes. Type 1 diabetes is a serious illness that cannot be cured, but it can be treated and controlled. With the number of cases expected to increase rapidly in the years to come, diabetes is a growing health challenge worldwide. Of the approximately 16 million diabetics in the United States, about 1.5 million suffer from type 1 diabetes. In this catabolic disorder afflicting predominantly young individuals, blood insulin is almost completely absent, leading to hyperglycemia and alterations in lipid metabolism. Type 1 diabetes is thought to be induced by a toxic or infectious insult that occurs in genetically predisposed individuals. With recent advances in the understanding of the involved immunology and cellular and molecular mechanisms, researchers strive to battle the disease with new preventive and corrective strategies2.